ASME 2012 Internal Combustion Engine Division Fall Technical Conference 2012
DOI: 10.1115/icef2012-92170
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Emission Characterization From a Natural Gas Fuelled High Pressure Direct Injection Engine

Abstract: High-Pressure Direct-Injection (HPDI) combustion of Natural Gas can reduce the gaseous and Particulate Matter (PM) emissions compared to a conventional diesel engine. Upcoming EPA and EURO emission limits may restrict particle number as well as particle mass. In preparation for these upcoming limits, the PM mass, size and composition was studied from a heavy-duty Cummins ISX engine converted to HPDI operation. To characterize the PM emissions, tests were based around a mid-speed, high-load operating point. Inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Patychuk and Rogak (2012) studied the PM mass, size, and composition while varying equivalence ratio (EQR), gas rail pressure (GRP), exhaust gas recirculation (EGR), injection timing, and diesel injection mass for a mid-speed (1500 RPM), high load (16.5 bar gross indicated mean effective pressure [GIMEP]) engine condition. They determined that PM mass emissions were affected primarily by EGR and EQR, and PM number emissions were also affected by EGR and EQR, and less strongly by GRP and diesel pilot quantity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patychuk and Rogak (2012) studied the PM mass, size, and composition while varying equivalence ratio (EQR), gas rail pressure (GRP), exhaust gas recirculation (EGR), injection timing, and diesel injection mass for a mid-speed (1500 RPM), high load (16.5 bar gross indicated mean effective pressure [GIMEP]) engine condition. They determined that PM mass emissions were affected primarily by EGR and EQR, and PM number emissions were also affected by EGR and EQR, and less strongly by GRP and diesel pilot quantity.…”
Section: Introductionmentioning
confidence: 99%
“…They determined that PM mass emissions were affected primarily by EGR and EQR, and PM number emissions were also affected by EGR and EQR, and less strongly by GRP and diesel pilot quantity. McTaggart-Cowan et al (2012) worked to reduce the PM mass emissions for the same engine mode used by Patychuk and Rogak (2012). They found that PM could be reduced by adjusting the relative phasing of the diesel and natural gas injections to allow for more premixing of the natural gas with air.…”
Section: Introductionmentioning
confidence: 99%
“…The PIDING combustion produces low, but still non-negligible soot concentrations, and is considered a challenging application for the FEN. Also, the PIDING research engine used here has well-characterized steady-state PM emission, 46,51,52 enabling us to make a targeted selection of relatively high soot-emitting operating points. More detailed information about the research engine can be found in McTaggart-Cowan 53 , Faghani 54 and the aspects of the system relevant to this work are briefly discussed here.…”
Section: Experimental Facility and Research Methodsmentioning
confidence: 99%
“…This is consistent with previous research on the same engine that operating conditions similar to points 4 and 7 could contain more than 20% volatile and semi-volatiles in the total PM mass. 51…”
Section: Validation Of the Fen C M And D M G Measurementsmentioning
confidence: 99%
“…However, special high-pressure gaseous injectors allow NG to be injected directly into the cylinder shortly before the end of the compression stroke [1]. This technology provides a better fuel economy and a more efficient combustion and has the key feature of both NG and diesel using a single injector [2,3]. We have two combustion modes according to the injection order of diesel and NG: High-pressure direct injection (HPDI, first injection of diesel and then NG) and partially premixed compression ignition (PPCI, first injection of NG and then diesel).…”
Section: Introductionmentioning
confidence: 99%